2019
DOI: 10.17494/ogusbd.554510
|View full text |Cite
|
Sign up to set email alerts
|

Matematik Derslerinde Matematik Tarihi Kullanımının Matematik Tutumuna Etkisi

Abstract: Bu çalışmada, matematik derslerinde matematik tarihi kullanımının öğrencilerin matematiğe olan tutumlarına etkisi incelenmiştir. Araştırmada verilerin elde edilmesi sürecinde deneysel desenlerden yarı deneysel desen olarak değerlendirilen ön test/son test eşitlenmemiş kontrol gruplu model kullanılmıştır. Araştırma, Erzincan ilinde bir ortaokulda farklı iki şubede bulunan 39 sekizinci sınıf öğrencisi ve bir ortaokul matematik öğretmeni ile gerçekleştirilmiştir. Çalışmada öğrencilerin matematik tarihi uygulamala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
(20 reference statements)
0
6
0
2
Order By: Relevance
“…Teachers think that the use of history of mathematics in textbooks will raise students' awareness of history of mathematics and provide resource support that they can benefit from. At the same time, it is stated that it can have positive results such as it will enable them to establish a connection between the existence of the subjects and their current state (Jahnke et al, 2002), to be inspired by famous mathematicians, and to encourage students to research history of mathematics (Başıbüyük & Soylu, 2019;İncıkabı et al, 2019). It has been concluded that when teachers encounter mathematics history items in textbooks, they feel the need to use them in their lessons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers think that the use of history of mathematics in textbooks will raise students' awareness of history of mathematics and provide resource support that they can benefit from. At the same time, it is stated that it can have positive results such as it will enable them to establish a connection between the existence of the subjects and their current state (Jahnke et al, 2002), to be inspired by famous mathematicians, and to encourage students to research history of mathematics (Başıbüyük & Soylu, 2019;İncıkabı et al, 2019). It has been concluded that when teachers encounter mathematics history items in textbooks, they feel the need to use them in their lessons.…”
Section: Discussionmentioning
confidence: 99%
“…Öğrenciler bu sayede geçmişte ortaya çıkan matematiksel bilgilerin günümüzü nasıl etkilediğini fark edebilirler (Jahnke vd., 2002). Öğrencilere matematiğin gelişim süreci gösterilerek yapılan buluşlardan ilham almalarını sağlamak ve onları yeni katkılar yapmaya özendirmek açısından da matematik tarihinin kullanımı önemli görülmektedir (Başıbüyük & Soylu, 2019;İncıkabı vd., 2019).…”
Section: Matematik Tarihi Ve Matematik Eğitimiunclassified
See 1 more Smart Citation
“…The role and significance of HoM in mathematics education has been emphasized with the renewal of the curriculum designed and implemented in line with the constructivist approach in 2005 by the Ministry of National Education (Ministry of National Education, [MoNE]) for the first time in our country. However, the parts allocated to HoM in mathematics textbooks were reduced in terms of quantity and quality by making them very limited with the curriculum update studies carried out in 2018 (Başıbüyük & Soylu, 2019;İncikabı et al, 2019;Mersin & Durmuş, 2018;Tan-Şişman & Gençkaya, 2021). This shortcoming may be an obstacle to the integration of HoM into lessons and hence, the lack of knowledge/experience that teachers have in this regard (Alpaslan & Işıksal-Bostan, 2016;Başıbüyük & Soylu, 2019;Yıldız & Baki, 2016;Yıldız & Baki, 2017).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…However, the parts allocated to HoM in mathematics textbooks were reduced in terms of quantity and quality by making them very limited with the curriculum update studies carried out in 2018 (Başıbüyük & Soylu, 2019;İncikabı et al, 2019;Mersin & Durmuş, 2018;Tan-Şişman & Gençkaya, 2021). This shortcoming may be an obstacle to the integration of HoM into lessons and hence, the lack of knowledge/experience that teachers have in this regard (Alpaslan & Işıksal-Bostan, 2016;Başıbüyük & Soylu, 2019;Yıldız & Baki, 2016;Yıldız & Baki, 2017). Indeed, the integration of HoM with mathematics education is considered vital for both teachers and students (Baki & Bütüner, 2018;Dündar & Çakıroğlu, 2014;Fried, 2008;İncikabı et al, 2019).…”
Section: Significance Of the Studymentioning
confidence: 99%